Inactivation of Pseudomonas deceptionensis CM2 on chicken breasts using plasma-activated water - Kang, Chaodi (J Food Sci Technol, 2019)
The aim of this study was to examine the effectiveness of plasma-activated water (PAW) for inactivating Pseudomonas deceptionensis CM2 on chicken breasts. Sterile distilled water (SDW) was activated by gliding arc discharge plasma for 60 s, which was defined as PAW60. The chicken breast samples inoculated P. deceptionensis CM2 were dipped in PAW60 or SDW for the indicated time intervals, respectively. After the treatment of PAW60 for 12 min, the population of P. deceptionensis CM2 on chicken breast was significantly reduced by 1.05 log(10) CFU/g (p < 0.05), which was higher than that of SDW-treated samples for the same time intervals (p < 0.05). The L* value of chicken breasts were increased whereas a* and b* values were decreased following PAW60 treatment, while there was no significant differences in the values of a* and b* between PAW60- and SDW-treated samples for the same time intervals (p > 0.05). As compared with SDW, PAW60 caused no significant changes in the texture characteristics (e.g. hardness, springiness, cohesiveness and gumminess) and sensory properties (e.g. appearance, color, odor, texture, acceptability). Thus, PAW can be very effective to improve microbiological safety of chicken breasts with resulting slight changes to the sensory qualities. This synergistic treatment of PAW with other non-thermal technologies should be well investigated in order to improve inactivation efficacy of PAW.